Design of a Web-Based Letter Disposition Information System in the Population Control and Family Planning Sector of the Banyuwangi Regency Social Service - Imroatin Nur Arifah; Navita Inka Ristiani; A.Hamdani (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This research aims to design a web-based letter disposition information system for the Population Control and Family Planning Sector of the Banyuwangi Regency Social Service. Mail management which is still done manually causes various problems, such as delays in the disposition process, risk of data duplication, and difficulties in searching mail archives. To overcome this problem, this research uses field research methods supported by literature study as a theoretical basis. System development was carried out using the Software Development Life Cycle (SDLC) approach using a prototype model which includes communication stages, rapid planning, system modeling, prototype development, and system implementation. The system designed includes features for managing incoming mail, outgoing mail, digital disposition, and electronic archiving of letters. The design results show that this system is able to increase efficiency, accuracy and transparency in the letter administration process, and is expected to become the basis for system development in the next implementation stage.